HUBUNGAN ANTARA PENGETAHUAN TENTANG PERKOPERASIAN DENGAN PARTISIPASI ANGGOTA DALAM BERKOPERASI (Survei pada Koperasi Pegawai Universitas Negeri Jakarta) - Nurhalim Sabang (Jurnal Ilmiah Econosains, 2011)
Abstract The objective of the research is to studies relationship between knowledge cooperation and participation cooperation. The research was carried out at Cooperation at State University of Jakarta (2003) with n = 50 respondents selected randomly. The research concludes that there is positive correlation between: (1) knowledge cooperation (X) and participation cooperation. Furthermore, there is positive correlation between knowledge cooperation and participation cooperation. Keywords: knowledge cooperation, participation cooperation.